2008
DOI: 10.1007/s00167-008-0580-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and structural results of partial supraspinatus tears treated by subacromial decompression without repair

Abstract: Patients with primary impingement and articular sided partial tears of the supraspinatus are often treated by subacromial decompression without repair, if the extent of the tear is estimated to be below 50% of tendon thickness. It has been questioned whether repair of these cuff lesions is necessary, because these tears could progress to full thickness tears with deteriorating clinical results. Our hypothesis was that subacromial decompression without repair of the supraspinatus tendon leads to significant cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 23 publications
0
37
0
1
Order By: Relevance
“…Surgical management options include arthroscopic debridement ± acromioplasty, in situ-repair, or tear completion with full-thickness rotator cuff repair. Several studies have reported excellent clinical outcomes with arthroscopic debridement and subacromial decompression for grade I and II tears [44,45]. However, in one study bursal surface tears were significantly more likely to fail than articular surface tears (29 vs. 3%, respectively) [42].…”
Section: Partial-thickness Rotator Cuff Tearsmentioning
confidence: 96%
“…Surgical management options include arthroscopic debridement ± acromioplasty, in situ-repair, or tear completion with full-thickness rotator cuff repair. Several studies have reported excellent clinical outcomes with arthroscopic debridement and subacromial decompression for grade I and II tears [44,45]. However, in one study bursal surface tears were significantly more likely to fail than articular surface tears (29 vs. 3%, respectively) [42].…”
Section: Partial-thickness Rotator Cuff Tearsmentioning
confidence: 96%
“…Debridement of rotator cuff tears has been known to be associated with a satisfactory short term results, especially in patients with low demands [47][48][49]. The goal of the surgery is to remove the sources of pain; therefore, the torn edges of the rotator cuff tendons are debrided and a gentle bursectomy is completed.…”
Section: Arthroscopic Debridement With or Without Long Head Of The Bimentioning
confidence: 99%
“…Insbesondere bei degenerativen artikularseitigen Partialrupturen der SSP-Sehne von weniger als 50% der Sehnendicke konnte gezeigt werden, dass ein Débride-ment mit einer subakromialen Dekompression ausreichend ist [6,20].…”
Section: Diskussionunclassified